(untitled) (Bangladesh Journal of Infectious Diseases, 2015)
Background: The biofilm production is an important phenomenon by bacteria such as Staphylococcus aureus that contribute to the multiple drug resistance. Moreover, biofilm formation by multidrug-resistant Staphylococcus aureus causes evading from immune responses. Objective: The aim of this study was to detect biofilm formation and presence of several related genes among multidrug-resistant (MDR) isolates of Staphylococcus aureus. Methods: This cross sectional study was conducted at a hospital in Tehran, Iran from July 2012 to January 2013. Patients admitted with the infections of the different sites of the body were selected as study population. Staphylococcus aureus isolates were collected from hospitalized patients and identified by conventional diagnostic tests. The multidrug-resistant MRSA isolates were detected by antibiotic susceptibility test. The phenotypic biofilm formation was detected by micro-titre tissue plate assay. The polymerase chain reaction (PCR) was performed to detect the mecA, Staphylococcal Cassette Chromosome mec (SCCmec) types, accessory gene regulatory (agr) genes, the icaADBC and several genes encoding staphylococcal surface proteins including clfAB, fnbAB, fib, eno, can, ebps and bbp genes with specific primers. Results: A total number of 209 Staphylococcus aureus were isolated of which 64 (30.6%) isolates were methicillin-resistant; among which 36(56.2%) isolates were MDR. These isolates were resistant to amoxicillin, tetracycline, ciprofloxacin, gentamicin, erythromycin and trimethoprim-sulfamethoxazole. All the isolates were susceptible to vancomycin and linezolid. All the MDR-MRSA harbored SCCmec type III. All the MDR- MRSA isolates were strong biofilm producers in the phenotypic test. Conclusions: Multidrug-resistant MRSA isolates produced biofilm strongly and the majority of these isolates harbored most of biofilm related genes. Bangladesh Journal of Infectious Diseases 2014;1(2):27-31